Technical analysis of the currency market : classic techniques for profiting from market swings and trader sentiment - Schlossberg, Boris (Wiley trading., 2006)
Proven currency-specific trading strategies from one of today's top currency analysts "If you trade currency, then you need to have this book on your desk. It's the only book you need for technical analysis of the fastest-moving market on the planet."--Rob Booker, Currency Trader, W.R. Booker & Company "In plain English, Schlossberg lays out the basics in using technical analysis to trade foreign currencies, from the fundamentals of how the FX market works to the variety of technical strategies and trade management techniques traders can employ. Along the way, he offers entertaining examples and observations as well as simple, easy-to-read charts and diagrams. Anyone interested in getting started in the hugely popular FX market would do well to begin with this book."--Sarah Rudolph, Executive Editor, SFO Magazine "Boris Schlossberg has done a fabulous job with this book. It's packed with insightful tips and strategies that are sure to save traders a lot of time and money."--Cory Janssen, CoFounder, Investopedia.com "Schlossberg's book is a great resource for traders just starting out in currency markets. His focus on simplicity is critical for a new trader's education on how to make money." -Andrew B. Busch, Global FX Strategist, BMO Financial Group